Etiology, Diagnosis, and Treatment of Leukorrhea - Damai Trilisnawati; Izazi Hari Purwoko; Mutia Devi; Suroso Adi Nugroho; Fitriani; Theresia L. Toruan (HM Publisher, 2021)
The most frequently reported complaints in the urogenital organ system is leukorrhea, also known as fluor albus. Leukorrhea is a discharge secreted from the genital organs, mostly occur in female. Leukorrhea has a significant incidence rate and varies according to many factors such as hormone and infection. Leukorrhea can be physiological in female, but when excess discharge is accompanied by other characteristics, the leukorrhea is considered pathological. This genital discharge also occurs in male for pathological reasons, mainly caused by infection. Several pathogenic infections, whether transmitted through secual contact or not, are the etiology of complaints of leukorrhea. Some specific pathogens will cause different symptoms in the two sex groups. To make a diagnosis, it is important for the examiner to carry out a detailed and coherent history, especially regarding sexual contact and a history of risky sexual behavior. Although some infections are asymptomatic, complications may occur if infections are not treated properly as early as possible. The management of leukorrhea is based on an examination and treatment algorithm with syndromic approach.